A multi-institutional prospective observational study to evaluate fascia iliaca compartment block (FICB) for preventing delirium in adults with hip fracture. Issue 1 (15th April 2022) - Salottolo, Kristin; Meinig, Richard; Fine, Landon; Kelly, Michael; Madayag, Robert; Ekengren, Francie; Tanner, Allen; Roman, Phillip; Bar-Or, David
Abstract : Objectives: Until recently, systemic opioids have been standard care for acute pain management of geriatric hip fracture; however, opioids increase risk for delirium. Fascia Iliaca compartment blocks (FICB) may be favored to systemic analgesia for reducing delirium, but this has not been well demonstrated. We evaluated the efficacy of adjunctive FICB versus systemic analgesia on delirium incidence, opioid consumption, and pain scores. Methods: This prospective, observational cohort study was performed in patients (55–90 years) with traumatic hip fracture admitted to five trauma centers within 12 hours of injury, enrolled between January 2019 and November 2020. The primary end point was development of delirium, defined by the Confusion Assessment Method tool, from arrival through 48 hours postoperatively, and analyzed with multivariate Firth logistic regression. Secondary end points were analyzed with analysis of covariance models and included preoperative and postoperative oral morphine equivalents and pain numeric rating scale scores. Results: There were 517 patients enrolled, 381 (74%) received FICB and 136 (26%) did not. Delirium incidence was 5.4% (n=28) and was similar for patients receiving FICB versus no FICB (FICB, 5.8% and no FICB, 4.4%; adjusted OR: 1.2 (95% CI 0.5 to 3.0), p=0.65). Opioid requirements were similar for patients receiving FICB and no FICB, preoperatively (p=0.75) and postoperatively (p=0.51). Pain scores were significantly lower with FICB than no FICB, preoperatively (4.2 vs 5.1, p=0.002) and postoperatively (2.9 vs 3.5, p=0.04). Conclusions: FICB demonstrated significant benefit on self-reported pain but without a concomitant reduction in opioid consumption. Regarding delirium incidence, these findings suggest clinical equipoise and the need for a randomized trial. Level of evidence: II—prospective, therapeutic.